PENGEMBANGAN ALAT PERMAINAN EDUKATIF ( APE ) JENIS BALOK UNTUK MENINGKATKAN KUALITAS PEMBELAJARAN DI TAMAN KANAK-KANAK - Johni Dimyati (Khazanah Pendidikan, 2011)
Point of view from this research is : what is the effort to develop education game tool can increase economic velue of waste wood and quality of teaching in Kindergarten in some aspects like students creativity, developing of cognitif, idea power, creativity power, psicomotoric, emotion, social and language of students ? The aim of this research are divided into two kinds ; a.Long range aim and b. Short range aim. Long range aim from this research are to build corporation among university ( Teacher Training and Education Faculty Muhammadiyah University of Purwokerto whit Education Institution of Early Age ( 1st, 2nd and 3rd Government Kindergarten of Dukuhwaluh Village, Kembaran District, Banyumas Regency. Advantage from this research are ; 1. Advantage from society economic view with encreasing of their income and opened of new job vacancy for wood craft with miking educative game tool made by waste wood; 2. Advantage from technology and science can add or enrich educatif game tool for education institution of early age; 3. Advantage for Teacher Training and Education Faculty Muhammadiyah University of Purwokerto can get data from result of this research about influence of Kindergarten; 4. Advantage for 1st, 2nd, and 3rd Government Kindergarten of Dukuhwaluh Village is gotten Educative Game Tool as cooperation with Teacher Training and Education Faculty of Muhammadiyah University of Purwokerto.Variable from this research are; increasing economic value of waste wood, wood craft creativity in making Educative Game Tool, creativity of Kindergarten Teacher in applicating of educative game tool. Method of collecting data from this research are observation, interview and documentation. Method of data analysis use statistic analysis of frecuensy distribution and fenomenologic. Conclution from this research are ; 1. Developing of educative game tool can increase economic value of waste wood; 2. Creativity of wood craft can be increased by making educative game tool; 3. Kindergarten Teacher can increase their creativity by applicating educative game tool in teaching activities either increasing of their process quality or students result; 4. Using educative game tool can add motivation and develop happines condition in teaching activities so can increase students creativity, cognitif, idea power, creativity power, psicomotoric, emotion, social and their language. Key words: Educative Game Tool, Economic Value , Teaching Quality of Kindergarten.